Soy Foods and Urinary Isoprostanes: Results from a Randomized Study in Premenopausal Women - Sen, Cherisse (2012)
In addition to their antiestrogenic effects, soy isoflavones may protect against cancer through alternate biologic actions including antioxidant properties. This randomized, crossover study explored the relation between dietary isoflavone intake through common soy foods and oxidative stress quantified by urinary isoprostane levels. Eighty-two women aged 39.2±6.1 years were randomized to a high soy diet of 2 soy food servings per day and a low soy diet of <3 servings per week for 6 months each, separated by a 1 month washout period. Urine samples were collected at baseline and at the end of each dietary period. Urinary isoprostane levels were measured using enzyme-linked immunosorbent assays (ELISA) and adjusted for creatinine levels. Mixed models using log-transformed values were applied to evaluate the effect of the high soy diet. Unadjusted isoprostane excretion levels were lower during the high than the low soy diet, but this effect was not statistically significant (p=0.81). After adjustment for urinary creatinine, isoprostane excretion was slightly higher during the high soy diet (p=0.02), an observation that was confirmed in a regression analysis between urinary isoflavones and isoprostanes during the high soy diet. The original association remained significant when restricted to adherent participants; however, this effect disappeared after exclusion of three extreme values. In agreement with several previous reports, these findings do not support the hypothesis that soy exerts antioxidant effects as measured by urinary isoprostane excretions, but additional markers of oxidative stress need to be investigated in future studies.